2014
DOI: 10.1080/15374416.2014.900717
|View full text |Cite
|
Sign up to set email alerts
|

A New Look at the Psychometrics of the Parenting Scale Through the Lens of Item Response Theory

Abstract: The psychometrics of the Parenting Scale's Overreactivity and Laxness subscales were evaluated using item response theory (IRT) techniques. The IRT analyses were based on two community samples of cohabiting parents of 3- to 8-year-old children, combined to yield an N of 852 families. The results supported the utility of the Overreactivity and Laxness subscales, particularly in discriminating among parents in the mid to upper reaches of each construct. The original versions of the Overreactivity and Laxness sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 34 publications
1
38
0
Order By: Relevance
“…We scored the answers on the basis of a two-factor model (overreactivity, laxness), according to recent studies (Lorber, Xu, Smith Slep, Bulling, & O'Leary, 2014;Salari, Terreros, & Sarjadi, 2012) that suggested that this model shows a better fit compared to the three-factor model, which also included a Verbosity subscale.…”
Section: Methodsmentioning
confidence: 99%
“…We scored the answers on the basis of a two-factor model (overreactivity, laxness), according to recent studies (Lorber, Xu, Smith Slep, Bulling, & O'Leary, 2014;Salari, Terreros, & Sarjadi, 2012) that suggested that this model shows a better fit compared to the three-factor model, which also included a Verbosity subscale.…”
Section: Methodsmentioning
confidence: 99%
“…PS scores distinguish clinical from nonclinical samples and have been validated against behavioral observations of parenting and with item response theory methods (Arney, Rogers, Baghurst, Sawyer, & Prior, 2008; Arnold et al, 1993; Harvey, Danforth, Ulaszek, & Eberhardt, 2001; Lorber, Xu, Slep, Bulling, & O'Leary, 2014). Parents rate their use of discipline strategies on the PS using 7-point scales that are anchored by one effective (e.g., sets limits on what my child is allowed to do) and one ineffective discipline strategy (e.g., lets my child do whatever he/she wants.).…”
Section: Methodsmentioning
confidence: 99%
“…Parents completed a 6-item version 1 of the Laxness subscale from the Parenting Scale, a self-report measure of discipline style validated against home observations [Arnold et al, 1993], and via item response theory methods [Lorber et al, 2014b]. Each item presents a discipline scenario (e.g., "When my child misbehaves") and asks the parent to identify the point that best describes their parenting along a 7-point continuum between 2 anchors.…”
Section: Methodsmentioning
confidence: 99%